Wringer - Spinelli, Jerry (New York : HarperCollins, 1997)
As Palmer comes of age, he must either accept the violence of being a wringer at his town's annual Pigeon Day or find the courage to oppose it.
"Joanna Cotler books."
Accelerated Reader
Keywords: Courage -- Fiction; Violence -- Fiction; Pigeons -- Fiction